Využití ultra vysokoúčinné kapalinové chromatografie s hmotnostní detekcí pro stanovení vitaminu D a jeho metabolitů pro klinickou praxi - Krčmová Kujovská, Lenka; Solichová, Dagmar; Sobotka, Luboš; Bláha, Milan; Červinková, Barbora; Kasalová, Eva (2016)
The project focuses on the development and validation of UHPLC methods for determination of vitamin D and its metabolites (25-OH D2, 25-OH D3) in human serum using modern technology. Method development is initiated by clinical research requirements of the Teaching Hospital in Hradec Kralove. Emphasis is placed not only on own research studies of vitamin D metabolism, but also on the speed and simplicity of the method, which would allow its introduction into routine examinations such as biochemical laboratories. The result of this study should be therefore an overview of the levels of vitamin D and its metabolites in selected groups of patients. After evaluation of the project should link of research activities in the field of analytical chemistry and clinical monitoring lead to better diagnostic capabilities and also improve treatments for serious civilization diseases and improve the care of individual patients.
Závěrečná zpráva o řešení grantu Interní grantové agentury MZ ČR
Keywords: Diagnostic Techniques and Procedures; separace krevních složek; Chromatography, High Pressure Liquid; hmotnostní spektrometrie; Blood Component Removal; vysokoúčinná kapalinová chromatografie; Mass Spectrometry; Hypercholesterolemia; chemie, klinická chemie; vitamin D; sérum; Serum; biochemická analýza krve; Cholesterol, LDL; klinické laboratorní techniky; Vitamin D; Blood Chemical Analysis; LDL-cholesterol; hypercholesterolemie; diagnostické techniky a postupy; biochemie; Clinical Laboratory Techniques